Digital Ethnographic Exploration of Media Narratives: Shaping Investment Decisions in Halal Tourism Ecosystems - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research investigates the influence of digital media narratives on investment decision frameworks within halal tourism ecosystems through digital ethnographic methodology. The study employs a comprehensive methodological approach incorporating systematic data collection across multiple digital platforms, including specialized forums, social media environments, and digital financial communities. Using mixed-methods analysis combining qualitative narrative assessment with quantitative lexicometric evaluation, the research reveals significant patterns in terminology frequency, with tourism-related terms dominating the discourse at 17,181 instances, followed by growth indicators (5,587), value measurements (4,678), and impact assessments (4,524). The business environment analysis identifies